Democracy on the Sidelines: The Erosion and Potential of Youth Sports as Democratic Education - Kurt Stemhagen; Kathy Hytten (AERA Open)
In this philosophical paper, we argue that youth sports, both in and out of schools, are a largely unrealized space for democratic/civic education. Where youth sports leagues used to be low cost, local, and inclusive, much has changed over the last several decades. We are now in the neoliberal era of exclusive, privatized, and professionalized youth sports. Drawing on Dewey’s robust conception of democracy and Talisse’s concerns about partisan polarization, we argue that youth sports should be spaces to develop democratic habits, dispositions, and values. We explore the benefits of youth sports as well as current challenges, including excessive costs and pressure, disrupted families, and hyperindividualism. We end by offering suggestions for reforming youth sports to recenter their educational and democratic potential and value, including supporting loosely structured play, modeling democratic behavior, teaching democratic habits directly, and learning from more progressive national sports models.